// End script hiding -->
SOLUTION: simplify the expression -4(-3x+y)-(-y-2x)
Algebra
->
Expressions
-> SOLUTION: simplify the expression -4(-3x+y)-(-y-2x)
Log On
Ad:
Mathway
solves algebra homework problems with step-by-step help!
Algebra: Evaluation of expressions, parentheses
Section
Solvers
Solvers
Lessons
Lessons
Answers archive
Answers
Click here to see ALL problems on expressions
Question 285829
:
simplify the expression -4(-3x+y)-(-y-2x)
Answer by
checkley77(12844)
(
Show Source
):
You can
put this solution on YOUR website!
-4(-3x+y)-(-y-2x)
12X-4Y+Y+2X
14X-3Y ANS.